Experimental Investigation of Volumetric and Mechanical Efficiency of the Leistritz L4 Multiphase Screw Pump - ZEGHDI Yahia; HOUGA Djamel Eddine; BOUDJELKHA Med Laid (Université of Eloued, 2025)
This thesis aims to evaluate the performance of the Leistritz L4 multiphase pump, focusing on volumetric and mechanical efficiencies under real operating conditions. Multiphase pumping technology enables the direct transportation of an oil–water–gas mixture without prior phase separation, thereby reducing investment and operating costs and limiting environmental impact. Experimental tests were carried out using a multiphase flow meter and the pump’s control system to monitor pressures, temperatures, flow composition, and electrical power consumption. The results showed that the volumetric efficiency ranged between 41% and 54%, influenced by the high associated gas fraction, while the mechanical efficiency ranged between 33% and 43% as a result of friction losses, thermal disturbances, and also the elevated gas content. This study highlights both the potential and the limitations of twin-screw multiphase pumps and provides practical recommendations to enhance their reliability and improve their energy efficiency in oil and gas industry applications تهدف هذه المذكرة إلى تقييم أداء المضخة متعددة الأطوار Leistritz L4 مع التركيز على الكفاءة الحجمية والكفاءة الميكانيكية في ظروف تشغيل واقعية. تُمكّن تقنية الضخ متعدد الأطوار من نقل خليط النفط والماء والغاز مباشرةً دون الحاجة إلى فصل مسبق، مما يساهم في تقليص تكاليف الاستثمار والتشغيل والحد من الأثر البيئي . أُجريت اختبارات تجريبية باستخدام جهاز قياس تدفق متعدد الأطوار ونظام التحكم بالمضخة من أجل مراقبة الضغوط ودرجات الحرارة ومكونات الجريان واستهلاك القدرة الكهربائية. أظهرت النتائج أن الكفاءة الحجمية تراوحت بين 41 % و 45 % متأثرة بارتفاع نسبة الغاز المرافق، في حين تراوحت الكفاءة الميكانيكية بين 33 % و 53 % نتيجة خسائر الاحتكاك والاضطراب الحراري وأيضًا بسبب الارتفاع الكبير في نسبة الغاز . تُبرز هذه الدراسة إمكانات ومحدوديات المضخات اللولبية ثنائية الدوران متعددة الأطوار، وتقدّم توصيات عملية من شأنها تحسين موثوقيتها ورفع كفاءتها الطاقوية في تطبيقات صناعات النفط والغاز .
Master's thesis specializing in energy.2025
Keywords: Multiphase pumping; twin-screw pumps; Leistritz L4 pump; volumetric efficiency; mechanical efficiency; pump performance; oil and gas industry.; الضخ متعدد الأطوار؛ المضخات اللولبية ثنائية الدوران؛ مضخة Leistritz L4 ؛ الكفاءة الحجمية؛ الكفاءة الميكانيكية؛ أداء المضخات؛ صناعة النفط والغاز.